Health consequences of migration in Micronesia - Garruto, Ralph M. (Array, 1990)
Migration within the Pacific basin is dramatically increasing as the process of acculturation and decreased isolation continues. Previously isolated groups living on small island ecosystems within Micronesia are experiencing altered patterns of disease morbidity and mortality as a result of migration that not only have far-reaching medical implications but sociocultural effects as well. It is clear that studies of migrant populations offer a unique opportunity for solving epidemiological and etiological problems of widespread medical significance, particularly when such studies involve not only the migrating population but the sending and receiving populations as well. The many examples of health consequences of forced and voluntary migration, and migration as a result of population pressure or natural disaster, may provide a better understanding